Dendritic Cell Migration to Skin-Draining Lymph Nodes Is Controlled by Dermatan Sulfate and Determines Adaptive Immunity Magnitude - Nadafi, Reza; Koning, Jasper J.; Veninga, Henrike; Stachtea, Xanthi N.; Konijn, Tanja; Zwiers, Antonie; Malmström, Anders; den Haan, Joke M. M.; Mebius, Reina E.; Maccarana, Marco; Reijmers, Rogier M. (Frontiers in Immunology, 2018)
For full activation of naïve adaptive lymphocytes in skin-draining lymph nodes (LNs), presentation of peptide:MHC complexes by LN resident and skin derived dendritic cells (DCs) that encountered antigens, is an absolute prerequisite. To get to the nearest draining LN upon intradermal immunization, DCs need to migrate from the infection site to the afferent lymphatics, which can only be reached by traversing a collagen dense network located in the dermis of the skin through the activity of proteolytic enzymes. Here, we show that mice with altered collagen fibrillogenesis resulting in thicker collagen fibers in the skin, display a reduced DC migration to the draining LN upon immune challenge. Consequently, the initiation of the cellular and humoral immune response was diminished. Antigen specific CD8+ and CD4+ T cells as well as antigen specific germinal center B cells and serum immunoglobulin levels were significantly decreased. Hence, we postulate that alterations to the production of extracellular matrix, as seen in various connective tissue disorders, may in the end affect the qualitative outcome of adaptive immunity.